2004
DOI: 10.1007/s00702-004-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Alzheimer’s disease clinical stage and Gq/11 in subcellular fractions of frontal cortex

Abstract: Alzheimer's disease (AD) is associated with impaired coupling of cell surface muscarinic cholinergic receptors to G proteins of the Gq/11 class in brain. This alteration may contribute to progression of cognitive impairment during the course of the disease. We hypothesized that increasing severity of cognitive impairment would be related to decreased levels of Gq/11 detected in key subcellular fractions made from postmortem brain tissue. In this study, we used Western blotting to determine the quantity of Gq/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We next sought to characterize the cytoplasmic, DSM and DRM fractions by reprobing blots with antibodies for Rap1, G olf , G i1 , G q/11 and PLCβ1–dopamine receptor-related signaling components whose subcellular localization has previously been characterized (Canobbio et al, 2008; Donati and Rasenick, 2005; Kelly et al, 2005). Rap1, G olf , G q/11 , G i1 and PLCβ1 were all found in the DSM (Fig 2).…”
Section: 0 Resultsmentioning
confidence: 99%
“…We next sought to characterize the cytoplasmic, DSM and DRM fractions by reprobing blots with antibodies for Rap1, G olf , G i1 , G q/11 and PLCβ1–dopamine receptor-related signaling components whose subcellular localization has previously been characterized (Canobbio et al, 2008; Donati and Rasenick, 2005; Kelly et al, 2005). Rap1, G olf , G q/11 , G i1 and PLCβ1 were all found in the DSM (Fig 2).…”
Section: 0 Resultsmentioning
confidence: 99%
“…Previous studies suggest that M 2 muscarinic receptor coupling via G i/o is preserved in AD brains (Cowburn, et al , 1992), but M 1 receptor coupling to G q/11 is reduced (Ladner, et al , 1995). Although the mechanisms contributing to a reduced coupling in AD remain unknown, it may relate to decreased levels of G q/11 (Kelly, et al , 2005). In fact, Kelly et al demonstrated a significant relationship between the levels of cognition and synaptic plasma membrane G q/11 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on isolated cells or subcellular fractions have used buffers containing EDTA (47,53), which may prevent the proper isolation of rafts (48). We have eliminated EDTA from our detergent-free buffer, but have added sodium fluoride and sodium orthovanadate to inhibit serine/threonine and tryrosine protein phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%